2016
DOI: 10.1111/apt.13810
|View full text |Cite
|
Sign up to set email alerts
|

Lactose malabsorption in systemic sclerosis

Abstract: Our study underscores the fact that lactose malabsorption often occurs in patients with systemic sclerosis. Furthermore, our findings highlight the fact that lactose breath test is a helpful, noninvasive method, by identifying the group of patients with systemic sclerosis with symptomatic lactose malabsorption that may benefit from a reduction in lactose intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
(110 reference statements)
0
18
0
Order By: Relevance
“…Following a 5‐week lactose‐free oral diet, symptomatic patients reported an overall reduction in GI symptoms ( P < 0.002) . Although results were significant, from quality assessment, the study has a moderate risk of bias due to poor study design …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Following a 5‐week lactose‐free oral diet, symptomatic patients reported an overall reduction in GI symptoms ( P < 0.002) . Although results were significant, from quality assessment, the study has a moderate risk of bias due to poor study design …”
Section: Resultsmentioning
confidence: 97%
“…A case‐control study indicated that the prevalence of lactose malabsorption was over 30% higher in patients with SSc compared with the controls ( P = 0.004) . Following a 5‐week lactose‐free oral diet, symptomatic patients reported an overall reduction in GI symptoms ( P < 0.002) . Although results were significant, from quality assessment, the study has a moderate risk of bias due to poor study design …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations